การผลิตปลาหมึกป่นเพื่อใช้เป็นส่วนประกอบอาหารกุ้ง - อุชุกร พฤกษ์พงศ์รัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 1987)
The general objectives of this study covered the development of squid meal processing techniques and the incorporation of squid meal into the compound feed for raising Jumbo tiger prawn (Penaeus monodon Fabricius) Squid meal processing techniques composed of preparation of raw materials, steam cooking, milling and drum drying. Four formulas of the experimental compound diet were set up. The first formula used fish meal as a protein source (control). The second formula used squid meal which was processed from the whole body of squid as a protein source. The third formula used squid meal which is processed from the squid wastes (visceral mass, skin and head at the ratio 1:1 : 1) as a protein source. The fourth formula used fish meal and squid wastes meal at the ratio of 1:1 as a protein source. The protein levels of these four formulas were adjusted at approximately 35%. The feeding trials were conducted with P-15 jumbo tiger prawn for a period of 12 weeks. The results showed that the fourth formula gave the best performance in terms of growth, survival, food conversion ratio and production, followed by formula 2, 3 and 1. The production costs of formula 1, 2, 3 and 4 were approximately 12.19, 12.06, 5.44 and 8.81 baht/kilogram, respectively.